Analisis Pengaruh Indeks Pembangunan Manusia (IPM) terhadap Ketimpangan Pengeluaran Kab/Kota di Provinsi Banten pada tahun 2020 - Pratama, Muhamad Teguh; Oktafiansyah, Fachrul; Desmawan, Deris (FEB Universitas Maritim Semarang, 2022)
The Human Development Index (HDI) & expenditure inequality for each province in Indonesia need to be studied whether the Human Development Index (HDI) and expenditure inequality in each district/city in Banten Province have an influence or not. The independent variable is the Human Development Index (HDI) and the dependent variable is expenditure inequality. The research method used is quantitative method using document data from the Central Statistics Agency (BPS) in Banten Province. The results showed that the Human Development Index (HDI) had no significant effect on expenditure inequality. Where if there is a decrease in the Human Development Index (IPM) it is not certain that it will reduce Inequality in Banten Province.